A review of public opinion towards alcohol controls in Australia - Livingstone Charles; Moodie A Rob; Tobin Claire (BMC, 2011)
Abstract Background Increasing concern about the negative impact of alcohol on the Australian community has renewed calls for tighter regulatory controls. This paper reviews levels of and trends in public support for liquor control regulations, regulation of alcohol promotions, and alcohol pricing and taxation reforms in Australia between 1998 and 2009. Methods Six electronic databases and twenty public health and alcohol organisation websites were searched for research literature, reports and media releases describing levels of public support for alcohol controls. Only studies which randomly selected participants were included. Results Twenty-one studies were included in the review. The majority of the Australian public support most proposed alcohol controls. Levels of support are divided between targeted and universal controls. Conclusions Implementation of targeted alcohol policies is likely to be strongly supported by the Australian public, but universal controls are liable to be unpopular. Policy makers are provided with insights into factors likely to be associated with higher public support.